Seed dispersal by black-backed Jackals (Canis mesomelas) and hairy-footed gerbils (Gerbillurus spp.) of !nara (Acanthosicyos horridus) in the central Namib Desert - Shikesho, Saima Dhiginina (Department of Biological Sciences, 2021)
This study investigated primary seed dispersal of !nara (Acanthosicyos horridus) by Blackbacked Jackals (Canis mesomelas) and secondary seed dispersal by scatter-hoarding hairyfooted gerbils (Gerbilliscus (Gerbillurus) spp.) in the central Namib Desert. This was accomplished by examining visitation rates and fruit removal of !nara melons, primarily by jackals. In addition, I determined the viability and germination rate of !nara seeds collected from jackal scat. The results indicate that jackals were the dominant species to visit !nara (93.3%) and the only !nara frugivores recorded by camera traps over two !nara fruiting seasons. There was no difference in the viability of ingested seeds and control seeds, but germination rates of ingested !nara seeds were significantly higher (50.4%) than control !nara seeds (34%). This component of the study suggests that Black-backed Jackals are the main primary dispersers of !nara seeds in the central Namib Desert. I furthermore examined secondary seed dispersal by tracking !nara seeds to determine whether scatter-hoarding hairyfooted gerbils were caching or consuming seeds. I recorded the distance moved, depth of seed burial, recovery rate and the habitats in which seeds were buried in three habitat types. Hairyfooted gerbils removed 100% !nara seeds from experimental sites and cached 60.3 % of all the !nara seeds removed. The gerbils frequently retrieved the buried caches within two days (77% of the time) and re-cached them elsewhere. The majority of caches were in the open areas (83%) and only consisted of one (39%) or two seeds (45%). Only 1.7% of the cached seeds were not retrieved by the gerbils during the 30-day observation periods. !Nara seeds were moved an average distance of 29.1±1.6 m and buried at an average depth of 4±0.2 cm. Although there is high probability of cache retrieval, some of the cached seeds survived. As gerbil caches are at favourable locations for plant establishment, and as it is more likely that buried seeds will survive until suitable conditions for germination and seedling establishment, seed dispersal by hairy-footed gerbils is advantageous to !nara plants. Therefore, hairy-footed gerbil species in the central Namib Desert contributed to secondary seed dispersal of !nara. The combined interaction of endozoochory by Black-backed Jackals (Canis mesomelas) and synzoochory by hairy-footed gerbils (Gerbillurus spp.) in dispersing seeds of !nara plants (Acanthosicyos horridus) in the central Namib Desert suggest diplochory is highly likely.